School inputs and learning outcomes in Mozambique : a quantitative analysis. - Beltran, Lina Maria (My University, 2015)
Quality education has been a major challenge, especially in the least developed countries where resources are limited and expansion of educational services has hindered the quality agenda. This research aims to identify which inputs and external interventions have the most significant effect on learning outcomes in the first cycle of Primary Education in Mozambique. A quantitative analysis was carried out in 1167 schools, including government schools with interventions supported by five international or local non-government organizations and a control group of government schools receiving no additional support. The findings of the linear regressions for each of the sample groups point towards text books being the school input with the most meaningful impact on pass rates regardless of the intervention (or lack of it), while teaching/learning in local languages to be the intervention yielding the most meaningful results.